Risk of Skin Cancer and Actinic Keratosis in Patients with Rosacea: A Nationwide Population-based Cohort Study - Soo Ick Cho; Hanjae Lee; Soyun Cho (Medical Journals Sweden, 2022)
The association between rosacea and skin cancer remains inconclusive, with conflicting reports. The aim of this nationwide population-based cohort study was to determine the risk of skin cancer in patients with rosacea. A rosacea cohort (n = 11,420) was formulated and evaluated from 2010 to 2019. The incidence rate ratios of actinic keratosis, cutaneous melanoma, keratinocyte carcinoma and gastric, colorectal, and liver cancer were analysed in comparison with a matched control group, and multivariable stratified Cox proportional hazards model analysis was performed. The risk of actinic keratosis and keratinocyte carcinoma was increased in the rosacea group compared with the control group, with adjusted hazard ratios of 6.05 (95% confidence interval 3.63-10.09) and 2.66 (1.53-4.61), respectively. The risk of cutaneous melanoma and gastric, colorectal and liver cancer was not increased, with adjusted hazard ratios of 1.69 (0.25-11.37), 0.81 (0.59-1.10), 0.91 (0.69-1.18) and 1.32 (0.89-1.95), respectively. These results reveal an increased risk of actinic keratosis and keratinocyte carcinoma in patients with rosacea.